Factor analysis of obsessive-compulsive disorder YBOCS-SC symptoms and association with 5-HTTLPR SERT polymorphism - Hasler, Gregor; Kazuba, Diane; Murphy, Dennis L. (American journal of medical genetics. Part B, Neuropsychiatric genetics, 2006)
Symptoms defining obsessive–compulsive disorder (OCD) are diverse. Factor analyses of OCD symptoms have been used to evaluate obsessive–compulsive phenotypes that are thought to be more homogenous than the macro phenotype. There is evidence that three factors (symmetry/ordering, obsessions/checking, and hoarding) are familial and preliminary evidence that repetitive rituals are associated with a functional polymorphism in the promotor region of the serotonin transporter gene (5‐HTTLPR). The goal of this study was to examine relationships between OCD symptom dimensions and 5‐HTTLPR. We genotyped 153 subjects who met DSM‐IV criteria for OCD. We used the Yale‐Brown obsessive–compulsive scale symptom checklist (YBOCS‐SC) to assess OCD symptoms. Using principle components analysis, we derived four factors from the 13 symptom categories of the YBOCS‐SC in this patient sample, which replicated previous factor analyses of this scale. The frequencies of the S allele and the SS genotype were associated with the second factor including obsessions regarding symmetry and compulsions involving repeating, counting, and ordering/arranging. This study may contribute to understanding of molecular genetic features underlying the appearance of symptom clusters in OCD. © 2006 Wiley‐Liss, Inc.